Ethical Leadership for the Professions: Fostering a Moral Community - Sama, Linda M. (Journal of business ethics, 2008)
This paper examines the professions as examples of “moral community” and explores how professional leaders possessed of moral intelligence can make a contribution to enhance the ethical fabric of their communities. The paper offers a model of ethical leadership in the professional business sector that will improve our understanding of how ethical behavior in the professions confers legitimacy and sustainability necessary to achieving the professions’ goals, and how a leadership approach to ethics can serve as an effective tool for the dissemination of moral values in the organization.